Hippocampal subfields in adolescent anorexia nervosa. (30th December 2018) - Myrvang, Anna D.; Vangberg, Torgil R.; Stedal, Kristin; Rø, Øyvind; Endestad, Tor; Rosenvinge, Jan H.; Aslaksen, Per M.
Highlights: Volume reduction found in 11 hippocampal subfields (HS) in adolescent AN. Hippocampal volume reduction may be more extensive than global volume reduction. Both gray and white matter HS reduced, contrasting previous findings in adults. Abstract: Patients with anorexia nervosa (AN) exhibit volume reduction in cerebral gray matter (GM), and several studies report reduced hippocampus volume. The hippocampal subfields (HS) are functionally and structurally distinct, and appear to respond differently to neuropathology. The aim of this study was to investigate HS volumes in adolescent females with restrictive AN compared to a healthy age-matched control group (HC). The FreeSurfer v6.0 package was used to extract brain volumes, and segment HS in 58 female adolescents (AN = 30, HC = 28). We investigated group differences in GM, white matter (WM), whole hippocampus and 12 HS volumes. AN patients had significantly lower total GM and total hippocampal volume. No group difference was found in WM. Volume reduction was found in 11 of the 12 HS, and most results remained significant when adjusting for global brain volume reduction. Investigations of clinical covariates revealed statistically significant relationships between the whole hippocampus, several HS and scores on depression and anxiety scales in AN. Results from this study show that young AN patients exhibit reduced volume in most subfields of the hippocampus, and that this reduction may be more extensive than the observed global cerebral volume loss.